Predictors of Intention to Use Maternity Waiting Home Among Pregnant Women in Bench Maji Zone, Southwest Ethiopia Using the Theory of Planned Behavior - Nigussie, Tadesse (Int J Womens Health, 2020)
BACKGROUND: Ending preventable maternal mortality remains an unfinished agenda and one of the world’s most critical challenges. Skilled care at birth is one of the crucial strategies that help to prevent deaths that occur during delivery. Maternity waiting homes have been endorsed to facilitate access to skilled care during intra-partum and post-partum periods for women living in rural areas. However, the majority of pregnant mothers in Ethiopia do not use this service; hence, this study aimed to assess the predictors of intention to use maternity waiting home. METHODS: A community-based cross-sectional study was conducted from March 15 to June 20, 2018 in Bench Maji Zone, Southwest Ethiopia. A multistage sampling technique was used. The data were collected by trained data collectors using a structured pre-tested questionnaire. Data were entered into the epi data manager version 4.0.2.101 and exported to SPSS version 21 for analysis. The correlation among constructs of the theory of planned behavior was estimated. A hierarchical linear regression was used to identify predictors of intention to use maternity waiting home, and α value of less than 5% was used as a level of significance. RESULTS: A total of 829 women were interviewed. The mean age of respondents was 27.1 (±5.2) years. Thirty-nine percent of the respondents used maternity waiting home previously. The attitude (β =0.12, p<0.001), subjective norm (β =0.47, p<0.001), perceived behavioral control (β =0.42, p<0.001), and ANC use during current pregnancy (β =0.07, p=0.030) were predictors of intension to use maternity waiting homes. R square was calculated to be 81%. CONCLUSION: The intention to use maternity waiting homes was significantly associated with antenatal care use, attitude, subjective norm, and perceived behavioral control. Thus, multidimensional interventions are important to increase the intension to use MWH.